Plastic surgery esthetics: what are these expectations? - Menegassi, Luana; Siqueira de Guimarães, Rafael (Revista de Psicologia, 2012)
It is possible to notice more and more women in the demand for fitness, beauty products and cosmetic surgery in search of an ideal of beauty, for which the image has become the engine for success and happiness, which brought the need for better understanding of what leads these women to seek for such practices of beautification. Given this we intend to unveil the expectations that drive these women to perform plastic surgery and understand the implications within. We used a qualitative approach and interviewed eight women aged between 20 and 35 years who had undergone surgery for silicone implants in the last 12 months, to whom was given a consent form and then applied a socio-demographic questionnaire and a semi-structured interview. Once collected the information, the interviews were subjected to content analysis. From the analysis we found the motivation, the expected developments, knowledge and feelings involving plastic surgery, but also the concept of beauty presented by the participants.